Portrait of Charents in post-Charents Armenian poetry - Gabrielyan, Vazgen (Bulletin of Yerevan University B: Philology, 2024)
It is undeniable that the poetry of Charents left a deep mark both on the Armenian poetry of his day and the following years. After the death of Charents, even during the period of ban on his name and works, the new generation of Armenian poets passed their literary path “under the spiritual auspices of Charents” (S. Kaputikyan). In those and especiallyin the following years, when Charents’ work became accessible to the public at large,intheir speeches and articles our poets, together with literary critics of the post-Charents era, repeatedly commented and valued the great poet’s work, his place and role in our poetry. The article is not about that portrayal in general, it focuses on their poetic conversations with Charents, references to the image of Charents in their poems, how Charents- the man and thepoet-was transformed in their poetic speech, to what extent it is visible as a character, as character-portrait, as if as a painting in fine art–both externally and internally, also in action. Many poems dedicated to Charents were written both in Armenia and in the Diaspora. Within the limits of the article, their reference is naturally limited. The poems of Gevorg Emin “Vision” (1937, December), Hrachya Hovhannisyan’s “ To the Dead Poet” (1940), Vahagn Davtyan’s “With Yeghishe Charents” (1977) and “Poetic Feast” (1977), Hrachya Hovhannisyan’s “Charents’ Lantern” (1988), are considered, as well as Davit Hovhannes’s triolet poem “REQUIEM AETERNAM In Memory of Yeghishe Charents” (1997), and Edward Militonyan’s collection “The Wizard of Fiery Legend” (2022), in which the great poet’s portrait, image, and the image of his time and tragic life are most visible. These poetic images certainly complement, in their own way, the respectable set of literary studies of Yeghishe Charents work that has been created up to now.